Oxidation of Different Microporous Carbons by Chemical and Electrochemical Methods - Berenguer, Raúl; Morallón, Emilia (Frontiers in Materials, 2019)
The functionalization of high surface area microporous carbon materials by oxidative treatments receives great interest for multiple applications. The micropore structure of the material and the oxidation method could play an important role in the process. In this work, we analyze and compare the effects of liquid-phase chemical and alternative electrochemical oxidation treatments in the textural and chemical properties of four microporous carbon materials, namely a granular-, cloth- and powder-like activated carbon (AC) and a powdery zeolite templated carbon (ZTC). Particularly, we provide new data on oxidation kinetics and changes on microporosity and surface chemistry of various microporous carbons. Characterization techniques reveal that the extent, textural changes and selectivity of the oxidation greatly depend on the type of microporous material and the oxidation method. The incorporation of surface oxygen groups (SOGs) generally causes a more-or-less significant decrease in the measured micropore volume and the specific surface area. In the studied ACs, the extent of oxidation and BET surface area reduction augment with their micropore volume, and the textural changes seem to be governed by the micropore blockage by SOGs. The disordered microporous structure of these materials is then quite robust towards oxidation, but its heterogeneity may contribute to the lack of selectivity during this process. By contrast, the regular micropore framework of the ZTC is rapidly destroyed even under soft oxidizing conditions, but it is proposed to promote certain selectivity during oxidation. The high reactivity and structural fragility of ZTC are assigned to the weak interconnections and large number of exposed edge sites in its structure. Our results demonstrate the fast oxidation rate of chemical treatments under different conditions, especially in the case of ZTC, what is proposed to restrict the control and to limit the oxidizability and selectivity of these functionalization processes. Contrarily, the electrochemical treatments are proved to better control the kinetics of oxidative functionalization, what may explain the observed higher efficiency and selectivity for SOGs introduction and the minimization of degradation in fragile microporous structures.